Yolk-shell MnO2 coated sulfur particles with excellent cycle stability for Li-S batteries. (9th October 2019) - Liu, Shoufa; Wang, Yinwei; Zhang, Ning; Xun, Qiao; Zhaofeng, Zhou
Abstract: Metal oxides have been recognized as ideal adsorbent materials for the soluble polysulfide in the Li-S batteries. Based on this theme, in our work, yolk-shell metal oxide MnO2 is prepared and designed as the host material for the element sulfur. The as-prepared yolk-shell S@MnO2 composites show excellent cycle stability as the cathode materials for the Li-S batteries. The novel structure of MnO2 /S composites could inhibit the dissolution of the polysulfide. Besides, it is beneficial for buffering the volume variation that caused during discharge-charging process. As a result, the as-prepared yolk-shell S@MnO2 composites show an initial specific capacity of 1156 mAh g −1 at the current density of 0.2 C.